ANALISIS POSTUR KERJA DENGAN METODE WORKPLACE ERGONOMIC RISK ASSESMENT PADA OPERATOR MESIN BUBUT MANUAL PADA PT YOGYA PRESISI TEHNIKATAMA INDUSTRI - Ferida Yuamita; Putri Rismantia (Lembaga Pengembangan Kinerja Dosen, 2022)
PT Yogya Presisi Tehnikatama Industri is a company engaged in manufacturing such as making molds, industrial machinery spare parts, automotive and plastic injection. The problem that occurs in this company is that there is activity on the lathe operator that has the potential to cause fatigue and pain complaints such as Musculoskeletal Disorders in workers, the results of filling out the NBM Questionnaire found that there were complaints on the back with a percentage of 56.25%, right forearm 62.5 %, 56.25% left thigh, 50% left knee, 50% right thigh, 68.78% right calf, 87.5% right ankle, and 87.5% right foot. So companies need to do an analysis related to posture of workers. One technique or method that can analyze work posture is the WERA (workplace ergonomic risk assessment) method.As for based on the analysis, the suggestions for improvement given are that the shoulders form a moderate position of less than 60o with more pauses, the wrists form an angle of less than 50° with repetitions of 0 to 10 times per minute, on the neck in a position of 10°-20° with movement increased pause. On the operator's back with a position of 0°-20° with 4-8 repetitions per minute, on the leg factor in a normal upright position, with a duration of less than 4 hours, on the contact stress factor the suggestion given is to improve the posture on the worker's wrist earlier. If it's more than 50o, it's best if the wrist posture is less than 50o. Meanwhile, from the results of data processing, a comparison of the final working posture scores obtained in the posture before the proposal was 39 for facing activities, and 38 for drilling and drilling activities included in the MEDIUM category. While the WERA score after the proposal is 26, which is included in the LOW category.